Effect of intermediate defense measures in voluntary vaccination games. (9th September 2016) - Iwamura, Yoshiro; Tanimoto, Jun; Fukuda, Eriko
Abstract: We build a model to reproduce the decision-making process of getting a vaccination based on the evolutionary game theory dovetailed with the SIR model for epidemic spreading. Unlike the two extreme options of whether or not getting a vaccination leads to perfect immunity, we consider whether 'intermediate defense measures' including masking, gargling, and hand-washing lead to imperfect effects of preventing infection. We consider introducing not only a 'third strategy' as a discrete intermediate measure but also a continuous strategy space connecting the cases of getting and not getting a vaccination. Interestingly, our evolutionary analysis suggests that the introduction of intermediate measures makes no difference for the case of a 2-strategy system in which only either getting or not getting a vaccination is allowed, even does not ameliorate, or say, gets worse to prevent spreading a disease. This seems quite different from what was observed in 2-player and 2-strategy (2  ×  2) prisoner's dilemma (PD) games with relatively stronger chicken-type dilemma than the stag-hunt one in which the introduction of middle-course strategies significantly enhances cooperation.